Nilai-nilai Kasus Perceraian di Kampung Tegal Selagalas Kecamatan Sandubaya Kota Mataram - Husnaini, Ninis Husna Januarita; I Wayan Karta; Filsa Era Sativa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify the values that contribute to divorce and to examine its impact on children involved in the process. The research employed a descriptive qualitative approach using a case study method, in which the researcher conducted direct fieldwork through observation and in-depth interviews with seven families who had experienced divorce in Kampung Tegal Selagalas, Sandubaya District, Mataram City. The findings reveal that divorce among the respondents was influenced by various value-related factors, with social and economic values being the most dominant. Based on these findings, it can be concluded that maintaining a balance of values within marriage is essential to prevent divorce and that special attention should be given to children affected by it.